2012
DOI: 10.18066/revunivap.v18i32.106
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento Da Equipe De Enfermagem Sobre O Protocolo Ressuscitação Cardiopulmonar No Setor De Emergência De Um Hospital Público

Abstract: RESUMO: O estudo teve como objetivo avaliar o conhecimento teórico e prático da equipe de enfermagem atuante na emergência sobre ressuscitação cardiopulmonar (RCP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
8
0
4
Order By: Relevance
“…13 Recognition of the rhythm and clinical history of the patient enables immediate behavior without loss of time, since rapid actions are essential. 17 Another important point that this study observed was the low level of knowledge of the nursing team regarding the heart rhythms that has indication of defibrillation and the initial load for this one. Moreover, asystole and EAWOP were frequently cited among shocking heart rates.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…13 Recognition of the rhythm and clinical history of the patient enables immediate behavior without loss of time, since rapid actions are essential. 17 Another important point that this study observed was the low level of knowledge of the nursing team regarding the heart rhythms that has indication of defibrillation and the initial load for this one. Moreover, asystole and EAWOP were frequently cited among shocking heart rates.…”
Section: Resultsmentioning
confidence: 87%
“…15 In addition to the identification of clinical signs, the diagnosis of CRA involves the recognition of the cardiac rhythm of the arrest, its cause and the actions that will be taken to reverse the CRA. 17 In this study, the minority of nurses and nurse technicians recognized all rhythms: non-pulse ventricular tachycardia, ventricular fibrillation, pulseless electrical activity, and asystole. 8 What differs from another study, in which 60% of professionals answered correctly about the possible rhythms found in CRA.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…12 Study carried out with nursing professionals showed that the interviewees know how to identify a CRA, which differs from the present study, since only students from the physical education course had positive results. 13 A negative factor was observed for most students since it shows that they do not understand the identification of the classic signs and symptoms of CRA, which may make it difficult to decide the immediate conduct that should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recognition of the patient's lack of response, respiration, pulse, or circulation signals is responsible for alerting the patient to need for fast and efficient support, avoiding serious damage to health. 12 Although the defibrillators / cardioversors identify the heart rhythms, it is of fundamental importance that the Nursing team is aware that in the extrahospital environment most CRP occur due to rhythms such as ventricular fibrillation (VF) and non-pulse ventricular tachycardia (NPVT), whereas in the hospital setting, pulseless electrical activity and asystole respond in most cases. This difference makes the ducts performed different, since early defibrillation is the only treatment for VF / non-pulse ventricular tachycardia.…”
mentioning
confidence: 99%